The role of aryl hydrocarbon receptor signalling in COVID-19 pathology and its therapeutic potential - Mbambara, Saidon; Modipane, Ndimo; Serite, Thato; Sathekge, Mike; Kgatle, Mankgopo (Frontiers in Molecular Medicine, 2025)
Coronavirus disease 2019 (COVID-19), caused by the betacoronavirus SARS-CoV-2, emerged in Wuhan, China, and rapidly evolved into a global health crisis. Recent evidence highlights the activation of the aryl hydrocarbon receptor (AHR) pathway following SARS-CoV-2 infection, implicating AHR in facilitating viral replication and impairing antiviral immunity. As a ligand-dependent transcription factor, AHR regulates immune responses, cellular differentiation, and proliferation, and is frequently exploited by viruses to evade host defences. In relation to COVID-19, AHR activation drives immune suppression, systemic inflammation, and metabolic disturbances, intensifying disease severity. Notably, in individuals with comorbidities such as obesity and diabetes, AHR overactivity exacerbates insulin resistance, oxidative stress, endothelial dysfunction, and thrombotic risk, contributing to cardiovascular complications. AHR also promotes airway remodelling and mucus hypersecretion, fostering respiratory dysfunction and fibrotic progression. This review synthesizes current insights into the mechanistic role of AHR signalling in SARS-CoV-2 pathogenesis and discusses its potential as a target for host-directed therapeutic interventions.